Contemporary Tafaqquh programme module in mosques : a review and proposal / Alias Azhar and Rahimin Affandi Abd. Rahim - Abd. Rahim, Rahimin Affandi (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
This paper focuses on the module development model for tafaqquh at the mosque in Kubang Pasu, Kedah. The tafaqquh programme has been systematically conducted jointly by JAKIM, the State Islamic Affairs Department and mosques' management committees. The programme has been made successful and effective by the contribution and cooperation of takmir teachers who have been appointed and trained intensively. These takmir teachers play very significant roles in the realisation of the aspiration and the scheme in developing knowledgeable society through the involvement of the mosque. To get the holistic view of the theme and subject of the study, focus is made on several key elements; the history of the development of tafaqquh programme module in the societies of the Malay Archipelago, Islamic education theory which correlates to the National Philosophy of Islamic Education : Studying fiqh method from the current methodology and pedagogy and finally the presentation of the current tafaqquh module of Alternative Islam in Malaysia. The learning of fiqh must be viewed from a broad context and it should be able to have an influence on the life of human beings from all living aspects.The Philosophy of Islamic Education, which is based on al-Quran and al-Sunnah should be able to be implemented realistically. The modification and upgrade of the studying fiqh syllabus in mosques require a drastic approach, besides practical module construction. Through these, it is hoped that the only learning of fiqh through the tafaqquh programme in mosques will progress on par with modernisation and current 'urf awareness in the society.